Comparative Genomic Analysis of Streptococcus dysgalactiae subspecies dysgalactiae Isolated From Bovine Mastitis in China - Xu, Siyu; Liu, Yang; Gao, Jian; Zhou, Man; Yang, Jingyue; He, Fumeng; Kastelic, John P.; Deng, Zhaoju; Han, Bo (Frontiers in Microbiology, 2021)
Streptococcus dysgalactiae subsp. dysgalactiae (SDSD) is one of the most prevalent pathogens causing bovine mastitis worldwide. However, there is a lack of comprehensive information regarding genetic diversity, complete profiles of virulence factors (VFs), and antimicrobial resistance (AMR) genes for SDSD associated with bovine mastitis in China. In this study, a total of 674 milk samples, including samples from 509 clinical and 165 subclinical mastitis cases, were collected from 17 herds in 7 provinces in China from November 2016 to June 2019. All SDSD isolates were included in phylogenetic analysis based on 16S rRNA and multi-locus sequence typing (MLST). In addition, whole genome sequencing was performed on 12 representative SDSD isolates to screen for VFs and AMR genes and to define pan-, core and accessory genomes. The prevalence of SDSD from mastitis milk samples was 7.57% (51/674). According to phylogenetic analysis based on 16S rRNA, 51 SDSD isolates were divided into 4 clusters, whereas based on MLST, 51 SDSD isolates were identified as 11 sequence types, including 6 registered STs and 5 novel STs (ST521, ST523, ST526, ST527, ST529) that belonged to 2 distinct clonal complexes (CCs) and 4 singletons. Based on WGS information, 108 VFs genes in 12 isolates were determined in 11 categories. In addition, 23 AMR genes were identified in 11 categories. Pan-, core and accessory genomes were composed of 2,663, 1,633 and 699 genes, respectively. These results provided a comprehensive profiles of SDSD virulence and resistance genes as well as phylogenetic relationships among mastitis associated SDSD in North China.